Bilateral ovarian endometriomas after laparoscopic hysterectomy following adjuvant tamoxifen therapy for breast cancer: A case report - Satoshi Nishiyama; Sotaro Hayashi; Naoki Abe; Sachino Kira; Miho Oda; Lifa Lee; Yoko To; Maki Goto; Hiroshi Tsujioka (Elsevier, 2022)
Tamoxifen, a selective estrogen receptor modulator, is widely used as adjunctive therapy for women with breast cancer. However, tamoxifen has an agonistic effect on the endometrium and may be associated with endometrial proliferation, hyperplasia, polyp formation and carcinoma. The case report describes a 50-year-old woman who developed bilateral ovarian endometriomas while taking tamoxifen for breast cancer after total laparoscopic hysterectomy. She had undergone total laparoscopic hysterectomy for multiple uterine fibroids with no ovarian pathology at age 48 years, had been diagnosed with breast cancer and had commenced tamoxifen as post-mastectomy adjuvant therapy. One year after starting tamoxifen, she developed bilateral ovarian swelling accompanied by acute abdominal pain. At laparoscopic bilateral salpingo-oophorectomy, endometriomas were visible on both ovaries. Pathological examination confirmed endometriotic cysts with no evidence of malignancy. Postoperatively, anastrozole (an aromatase inhibiter) was substituted for tamoxifen as adjuvant therapy for her breast cancer.